ANALISIS PENGARUH PENAMBAHAN IJUK 0,25% DAN 0,5% PADA CAMPURAN BETON fc’ 14,5 MPa (NON STRUKTUR) - Haristha, Yosi; Bastian, Elfania (Rang Teknik Journal, 2022)
Concrete is the majority of materials used in construction in Indonesia in general. Concrete mix innovations are needed so that concrete has better quality and quality. Innovation in concrete mixture one of them by using organic waste. In addition to improving quality, organic waste used is expected to reduce global warming. In Nagari IV Koto Palembayan ijuk from enau trees is not processed and left alone, so over time the ijuk can become waste. In this study discussed the effect of the addition of ijuk in the concrete mixture against the strong press of concrete. The targeted concrete press strong value is 14.5 MPa. The test object is made by varying the amount of ijuk addition in the concrete mixture by 0.25% and 0.5%. The test object used is a cylinder measuring 15cm in diameter and 30 cm high. Testing was conducted when the concrete was 7 days old, 14 days and 28 days old using 2 samples of test objects. The results showed a strong value of normal concrete press age of 28 days obtained at 15.57, while the strong value of additional concrete press ijuk 0.25% and 0.5% obtained by 19.82 MPa and 18.26 MPa. The results showed additional concrete ijuk 0.25% increased by 27.30% from the normal concrete press strength and the strong value of additional concrete press ijuk 0.5% also increased by 17.28% from the strong normal concrete press.